Apoptotic neutrophils undergoing secondary necrosis induce human lung epithelial cell detachment - Liu, Chien-Ying (J Biomed Sci, 2003)
Clearance of apoptotic neutrophils by alveolar macrophages plays an important role in the resolution phase of lung inflammation. If not cleared, apoptotic neutrophils are postulated to release histotoxic granular contents. Since numerous cellular proteins are degraded during apoptosis, we sought to determine whether functional serine proteinases are indeed released by apoptosing neutrophils in vitro. In a coculture system, cytokine-activated neutrophils induced detachment in the human epithelial cell line, A549. This process was CD18- and serine proteinase-dependent. Early apoptotic neutrophils induced significant detachment, but live, senescent, resting neutrophils and terminal, secondary necrotic neutrophils had a different effect. This detachment process was CD18-independent but serine proteinase-dependent. Similarly, detachment occurred with primary human small airway epithelial cells. Notably, epithelial cell detachment correlated with the transition of early apoptotic neutrophils to secondary necrosis and with the accumulation of elastase in the supernatant. The membrane integrity of lung epithelial cells was damaged in advance of significant cell detachment. These observations suggest that not only live activated neutrophils but also apoptosing neutrophils can reveal functional elastase activities. Furthermore, the rapidity of the transition emphasizes the importance of the prompt clearance of apoptotic neutrophils before they progress to secondary necrosis at the site of lung inflammation.